Plant-derived essential oils affecting settlement and oviposition of Bemisia tabaci (Genn.) biotype B on tomato - Baldin, Edson L.L. [UNESP]; Crotti, Antônio E.M.; Wakabayashi, Kamila A.L.; Silva, José P.G.F. [UNESP]; Aguiar, Gabriela P.; Souza, Efrain S. [UNESP]; Veneziani, Rodrigo C.S.; Groppo, Milton (Springer Nature, 2013)
The silverleaf whitefly Bemisia tabaci (Genn.) biotype B (Hemiptera: Aleyrodidae) is an economically important pest of tomatoes Solanum lycopersicum (L.), causing irregular ripening on fruits and transmitting several plant pathogenic geminiviruses. The management of this pest is commonly based on repetitive spraying with synthetic pesticides, causing serious environmental damages and increase of resistance by insect population. In the present study, essential oils from the leaves of Artemisia camphorata Vill., Ageratum conyzoides L., Foeniculum vulgare Mill., Lippia alba (Mill.) N. E. Br., Plectranthus neochilus Schltr., and Tagetes erecta L. were investigated for their possible repellent and oviposition-deterrent effects against B. tabaci biotype B on tomato. In a multi-choice assay, P. neochilus essential oil was the most active repellent and oviposition deterrent. Essential oils of A. conyzoides and T. erecta significantly deterred the female B. tabaci biotype B from laying eggs on treated tomato leaflets compared with the control. (E)-Caryophyllene (30.67 %) and the monoterpenes α-pinene (15.02 %) and α-thujene (11.70 %) were identified as the major constituents of the essential oil of P. neochilus. Our findings demonstrated the potential of essential oil of P. neochilus and other oils in the reduction of settlement and oviposition of B. tabaci biotype B on tomato. © 2012 Springer-Verlag Berlin Heidelberg.
Keywords: Deterrence; Essential oil; Plectranthus neochilus Schltr; Silverleaf whitefly; angiosperm; biotype; essential oil; oviposition; pest control; pest species; pesticide application; whitefly; Ageratum conyzoides; Aleyrodidae; Artemisia; Bemisia argentifolii; Bemisia tabaci; Foeniculum vulgare; Geminiviridae; Hemiptera; Hexapoda; Lippia; Lippia alba; Lycopersicon esculentum; Plectranthus; Tagetes erecta